If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1y = 2x + -1 Reorder the terms: x + 1y = -1 + 2x Solving x + 1y = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. x + -2x + 1y = -1 + 2x + -2x Combine like terms: x + -2x = -1x -1x + 1y = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 -1x + 1y = -1 + 0 -1x + 1y = -1 Add '-1y' to each side of the equation. -1x + 1y + -1y = -1 + -1y Combine like terms: 1y + -1y = 0 -1x + 0 = -1 + -1y -1x = -1 + -1y Divide each side by '-1'. x = 1 + y Simplifying x = 1 + y
| g(1)=2(1)+4 | | 6a+6=4a-1 | | 3x-2+4x+x+12=66 | | 12x^2+18=30 | | mp+mq=r | | 3(x-4)=2(x-3) | | 21x-6+5=26 | | 5v-9=3v+1 | | 3(5-5)= | | 88=7x+5x+4 | | -12x+7=4x-9 | | 7v-9=4v+3 | | 81t^2-144t+64= | | 5(2+t)-2(t+1)= | | 6v-4=5v+4 | | 16s^2-56s+49= | | b=75+(15+6)w | | (-2xy^2)(3x^2y^4)= | | x(x+7)=120 | | v-5/3-v=-3(v-1) | | 8n-(6n+5)=7 | | 190-2x+x+10=180 | | 2x-1=y | | 2x+10=y | | 4+4x/3=6 | | 2x-13=y | | -3x+5=y | | 3x+6=33 | | 13=-3x-8 | | (3x-1)(x+4)= | | 2y-6y+8=2(-2y+9) | | 10x^2-20=-5x |